The Role of Monetary Sterilization Mechanisms in Achieving Monetary Stability in Iraq: An Econometric Analysis - Kovan Tamar Ghazi; Hivi Azeez Sabri; Bahaa Mohammed Khalid (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Achieving monetary stability remains a critical challenge for Iraq, primarily due to its heavy reliance on oil revenues and heightened vulnerability to external financial shocks. The volatility of global oil prices and frequent fiscal imbalances have complicated the Central Bank of Iraq’s (CBI) efforts to maintain monetary equilibrium. This study investigates the effectiveness of the monetary sterilization mechanism in stabilizing Iraq’s monetary environment between 2004 and 2023. Using annual data from official sources, primarily the CBI, the research employs an econometric approach, integrating a deductive methodology with descriptive analysis and quantitative modelling. The study estimates the sterilization coefficient and evaluates its impact on key monetary indicators, including inflation and exchange rate stability. The findings reveal that sterilization policies have a statistically significant effect on short-term monetary stability, mitigating immediate price and currency volatility. However, the long-term impact is statistically insignificant, largely due to structural economic limitations, such as the predominance of oil exports, shallow financial markets, and restricted monetary policy tools. The empirical results suggest that Iraq practices partial rather than full sterilization, leading to residual inflationary and deflationary pressures. The study recommends developing more diverse and sustainable monetary policy instruments, strengthening coordination between monetary and fiscal policies, and promoting economic diversification to achieve enduring monetary stability.